Fiscal Correction Analysis of Commercial Financial Reports at Cv. Bandung Nation's Hope for 2022-2023 - Garin, Muhammad; Audina, Bella Puspita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research is a qualitative research that aims to find out the financial statements on CV. Hope of the Nation according to Financial Accounting Standards and Income Tax Law. By conducting fiscal reconciliation, the Company simply made corrections to different items. A positive correction will increase taxable income, while a negative correction will reduce taxable income. The method used in this study is descriptive qualitative, with data collection techniques of interviews, questionnaires, observations and documentation. The results of this study show a Positive Correction in Vehicle Depreciation Costs in 2022-2023 from Rp. 612,191,875 to Rp. 306,095,938 and also in Consumption Costs in 2022 from Rp. 2,894,237 to Rp. 1,447,119 and in 2023 from Rp. 5,324,288 to Rp. 2,662,144 which means that if the correction is positive then these costs will increase commercial profits and after correction the value will become fiscal profit or taxable income.